2016
DOI: 10.1016/j.advwatres.2016.03.015
|View full text |Cite
|
Sign up to set email alerts
|

Pore-scale supercritical CO2 dissolution and mass transfer under imbibition conditions

Abstract: In modeling of geological carbon storage, dissolution of supercritical CO 2 (scCO) is often assumed to be instantaneous with equilibrium phase partitioning. In contrast, recent corescale imbibition experiments have shown a prolonged depletion of residual scCO 2 by dissolution, implying a non-equilibrium mechanism. In this study, eight pore-scale scCO 2 dissolution experiments in a 2D heterogeneous, sandstone-analogue micromodel were conducted at supercritical conditions (9 MPa and 40 °C). The micromodel was fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
47
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 53 publications
(48 citation statements)
references
References 42 publications
(55 reference statements)
1
47
0
Order By: Relevance
“…With similar core characteristics, the injection flow rate was much lower than the velocities in the dissolution experiment in the literature [9]. Therefore, the dissolution mechanism dominated during the brine imbibition and CO 2 gradually dissolved in the pore space as the brine injection continued.…”
Section: Resultsmentioning
confidence: 72%
See 3 more Smart Citations
“…With similar core characteristics, the injection flow rate was much lower than the velocities in the dissolution experiment in the literature [9]. Therefore, the dissolution mechanism dominated during the brine imbibition and CO 2 gradually dissolved in the pore space as the brine injection continued.…”
Section: Resultsmentioning
confidence: 72%
“…However, characteristics of flow development indicated that brine tended to avoid the gaseous CO 2 clusters, implying lower dissolution rates and less probability of dissolution events. In the previous study, imbibition of unsaturated brine was more focused and had a lower sweep efficiency [9]. Taking the efficiency into account, the comparison of our results indicates that the supercritical CO 2 demonstrates its superiority to improve the trapping efficiency of CO 2 sequestration during the imbibition.…”
Section: Pore-scale Co 2 Dissolution and Flow Developmentmentioning
confidence: 91%
See 2 more Smart Citations
“…More recently, these findings have been applied to the field of GCS. For instance, Chang et al (2016) showed that the depletion of supercritical CO 2 occurred more slowly when the CO 2 saturation was higher, but that the dependence of the mass transfer rate on saturation was not necessarily monotonic. Likewise, Jiang et al (2017) showed that the rate of CO 2 gas dissolution into brine was slow when gas saturation was high, then the rate increased as gas saturation decreased, and then decreased again as the last of the gas disappeared.…”
Section: Water Resources Researchmentioning
confidence: 99%